2018
DOI: 10.1093/icesjms/fsy135
|View full text |Cite
|
Sign up to set email alerts
|

Pelagic habitat and offspring survival in the eastern stock of Atlantic bluefin tuna

Abstract: In this manuscript, we test how an understanding of geographical variation in larval fitness in relation to temperature and habitat use could be a useful method to improve our understanding of recruitment and develop better indices of annual recruitment. On the basis of the assumption that growth and survival of tuna larvae are influenced by temperature, we have developed a potential larval survival index for Atlantic bluefin tuna (Thunnus thynnus) by combining empirical data from egg and larval rearing experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Arrizabalaga et al () also found these environmental preferences for BFT species in a broad study covering the Atlantic, Pacific, and Indian oceans. Even though the preferential thermal range derived from the model was much lower than the recognized spawning temperature threshold of 24°C (Schaefer, ), recent estimations set the thermal conditions of the spawning season onset closer to our results (Alemany et al, ; Gordoa & Carreras, ; Reglero, Balbín, et al, ; Reglero, Ortega, et al, ). In addition, greater BCPUEs were found related to negative SLA, an indicator of mesoscale cyclonic eddies, which associated with increased productivity (Biggs & Muller‐Karger, ; Gasca, ) have been recognized as key areas for reproduction and recruitment of many fish species (Bakun, ; Condie & Condie, ; Condie, Mansbridge, & Cahill, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Arrizabalaga et al () also found these environmental preferences for BFT species in a broad study covering the Atlantic, Pacific, and Indian oceans. Even though the preferential thermal range derived from the model was much lower than the recognized spawning temperature threshold of 24°C (Schaefer, ), recent estimations set the thermal conditions of the spawning season onset closer to our results (Alemany et al, ; Gordoa & Carreras, ; Reglero, Balbín, et al, ; Reglero, Ortega, et al, ). In addition, greater BCPUEs were found related to negative SLA, an indicator of mesoscale cyclonic eddies, which associated with increased productivity (Biggs & Muller‐Karger, ; Gasca, ) have been recognized as key areas for reproduction and recruitment of many fish species (Bakun, ; Condie & Condie, ; Condie, Mansbridge, & Cahill, ).…”
Section: Discussionsupporting
confidence: 84%
“…An appropriate spatiotemporal management strategy involves understanding the spatial distribution of both target and bycatch species and the environmental factors forcing those distributions (Cruz, Machete, Menezes, Rogan, & Silva, ; Druon, Fromentin, Aulanier, & Heikkonen, ; Fromentin & Powers, ; Roe et al, ; Williams, Kirby, & Beverly, ). Previous studies have linked ABFT distribution with environmental features within feeding (Druon et al, ; Royer, Fromentin, & Gaspar, ) and spawning grounds in both the Mediterranean Sea (Alemany et al, ; Druon et al, ; Muhling et al, ; Reglero, Balbín, et al, ) and the GoM (Muhling, Lamkin, & Roffer, ; Muhling et al, ; Teo & Block, ; Teo, Boustany, Block, & a., ). Research in the GoM has focused mainly on US waters, leaving a significant information gap concerning the Mexican part of the Gulf.…”
Section: Introductionmentioning
confidence: 99%
“…Massutí and Morales‐Nin (1995) suggested a spawning migration of adult dolphinfish from Atlantic waters to Mediterranean spawning grounds similar to the well‐documented migration of bluefin tuna spawners. Nonetheless, the two cases differ in that the spawning of Atlantic bluefin tuna does not take place until the migrants are well into the Mediterranean, beyond the Alboran Sea (Medina et al ., 2002; Reglero et al ., 2019). In contrast, as shown here, the dolphinfish does spawn in the GoC during summer months (July through September).…”
Section: Resultsmentioning
confidence: 99%
“…The recovery of the Eastern Atlantic bluefin tuna population during the last decade, after a long period of continuous and alarming decrease, is a successful example of how science and operational oceanography can trigger advances in the sustainability of fisheries and species conservation. At SOCIB, the combination of hydrodynamic models, remote sensing and in situ data has enabled the development of techniques for predicting both the spawning and larval habitat distribution, and the survival rate of the egg and larvae in the Balearic Sea (Álvarez-Berastegui et al, 2016;Reglero et al, 2018). These novel predictive capabilities have been applied to the standardization of larval abundance indices used to evaluate the trends of adult tuna populations during the last two decades (Ingram et al, 2017;Álvarez-Berastegui et al, 2018a), and to integrate environmental variability into the short-term forecasting of the survival of larvae and the derived immature individuals.…”
Section: Mediterranean Sea Environmental and Climate Challengesmentioning
confidence: 99%